THE PENJABARAN 《六德》DALAM SLIP BAMBU GUODIAN - Yohan Yusuf Arifin (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
《六德》is one of the moral teachings in Confucianism contained in the Guodian bamboo slip, discuss about the relationship between humans which aims to shape the relationship between humans to be better and more harmonious.This research try to describe the content of the teachings of 《六德》in Gudian bamboo slips so that we can find out the meaning to be conveyed from these teachings.This research is a qualitative descriptive study that uses 《六德》as the main reference and is supported by other literature sources that are related to Confucian teachings.Hopefully that the results of this study can provide useful information for those studying Confucianism and a reference for similar research.